Complexities in the Provision of Respite Care to Family Carers of Persons with Intellectual Disabilities - Frieda Finlay; Anne Lawlor; Ray McConkey; Patricia O'Brien; Hasheem Mannan; Gerry Harrington (Disability, CBR and Inclusive Development)
Purpose Respite care is generally thought to benefit family carers of persons with intellectual disabilities and is regarded as an important component of family-centred services.  However, the complexities associated with the provision of such services, from the carer’s perspective, have been rarely investigated. Method This qualitative research study was carried out through a participatory action research process that involved collaboration among researchers and family members as co-researchers.  Seven focus groups, involving seventy family carers (fifty mothers, fifteen fathers and five sisters), were held in seven locations across the Republic of Ireland.   Results Three main themes dominated the discussions.  The first theme related to the ambivalence of carers towards using respite services, as expressed in their reluctance to relinquish care-giving for even a short period; the feelings of guilt they experienced; and the greater needs of other carers.  The second theme related to the benefits of respite breaks, but these were solely with respect to the carer and other family members, rather than to the person with an intellectual disability.  The third theme regarding the quality of provision was dominated by concerns for the care the person received in using the services.   Conclusions Respite care has the potential to make a difference, and these findings call for building much- needed alliances between all members of the family and professionals.  This is in order to support one another through the difficulties associated with the redesign of existing respite provision, and the extension of these services to the growing number of carers who require respite breaks. doi 10.5463/DCID.v22i2.22 Key words Intellectual disability, respite, family members, Ireland